Forecasting global flows - Edith Skriner (Institute for Advanced Studies (IHS), 2007)
The theory suggests that investment activities and monetary policy influence the development of the global business cycle. The oil price and other raw material prices also play a key role in the economic development and there is a co-movement among oil consumption and global output. Therefore, the aim of this study is to explain the development of this set of variables by ARs, small-scale VARs and ECMs. The lag length and the rank of the time series models have been determined using information criteria. Then one-step ahead forecasts have been generated. It was found, that the ARs generate the best forecasts at the beginning of the forecasting horizon. However, when the forecasting horizon increases the VARs outperform the ARs. Comparing the forecasting performance of the ECMs, it was found that the forecasting ability of the ECMs in first differences outperform the level based ECMs when the forecasting horizon increases.
Keywords: F17; C22; C5; 330; international economics; time series models; forecasts; forecast evaluation; Internationale Wirtschaftsbeziehungen; Kapitalmobilität; Risikomaß; Prognoseverfahren; Welt